1994
DOI: 10.2166/wst.1994.0451
|View full text |Cite
|
Sign up to set email alerts
|

Active oxygen species generated during chlorination and ozonation

Abstract: In water treatment, ultraviolet irradiation, ozonation, and chlorination are believed to produce various active oxygen species, which seem to participate in reactions with fumic acid, pollutants and bacteria. It was, however, very difficult to determine the actual kinds and amount of active oxygen during the processes because of deficiencies of method. In order to determine the kinds and amounts of active oxygen species which may participate in water treatment process, the spin-trapping ESR (electron spin reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
17
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
10
17
0
1
Order By: Relevance
“…6(a), the spectrum was composed of quartet lines having peak height ratio of 1:2:2:1. The ESR parameters coincided with those of typical DMPO-OH adduct [16], and the result confirmed that the quartet signal is DMPO-OH adduct.…”
Section: Esr Analysissupporting
confidence: 70%
“…6(a), the spectrum was composed of quartet lines having peak height ratio of 1:2:2:1. The ESR parameters coincided with those of typical DMPO-OH adduct [16], and the result confirmed that the quartet signal is DMPO-OH adduct.…”
Section: Esr Analysissupporting
confidence: 70%
“…The spectrum was composed of quartet lines having peak height ratio of 1:2:2:1. The ESR parameters coincided with those of typical DMPO-OH adduct (Utsumi et al, 1994). The signal strength of DMPO-OH adduct represents the amount of Å OH radical to some extent during ozonation.…”
Section: Generation Of Hydroxyl Radicalssupporting
confidence: 63%
“…In terms of applications to semiconductor manufacturing, ozonized water cleaning systems are strongly desired as they provide enhanced removal rates for organic contaminants. In addition, the challenge to the amorphous carbon like damage layer created by ion-implant doses greater than 5E14/cm 2 is significantly important to introduce the ozone cleaning method in the semiconductor manufacturing processes [10,11].…”
Section: Introductionmentioning
confidence: 99%